2014
DOI: 10.1161/hypertensionaha.113.02303
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic CCAAT/Enhancer Binding Protein–Associated Changes of DNA Methylation in the Angiotensinogen Gene

Abstract: A ngiotensinogen (AGT; serpin peptidase inhibitor, clade A, member 8) is a glycoprotein that is the primary substrate of the renin-angiotensin-aldosterone system (RAAS) and is, therefore, one of the most frequently studied proteins because of its contributions to hypertension. Given that AGT is the primary substrate controlling the rate-limiting step of the production of angiotensin peptides, a rise in AGT levels can lead to a parallel increase in the formation of the physiologically active enzyme angiotensin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 39 publications
7
30
0
1
Order By: Relevance
“…It is involved in both transcriptional activation and suppression, and recent evidence has implicated C/EBPb in the transcriptional silencing of miRNAs such as let-7i, miR-145, and miR-155 (53,63). Accessibility of promoters to C/EBPb depends on H3 methylation status at the C/EBPb binding region, as demonstrated previously (64,65). Indeed, H3 methylation was detected in the proximal region of the miR-155 and miR-146a promoters (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…It is involved in both transcriptional activation and suppression, and recent evidence has implicated C/EBPb in the transcriptional silencing of miRNAs such as let-7i, miR-145, and miR-155 (53,63). Accessibility of promoters to C/EBPb depends on H3 methylation status at the C/EBPb binding region, as demonstrated previously (64,65). Indeed, H3 methylation was detected in the proximal region of the miR-155 and miR-146a promoters (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…However, very little is known about where and how changes in DNA methylation take place in non‐CpG island promoters. We have recently shown that interleukin 6 stimulation can cause DNA demethylation of the angiotensinogen gene promoter in H295R cells 20. In our data, switching from a low‐salt diet for 4 weeks to a high‐salt diet for 4 weeks decreased aldosterone synthesis and induced hypermethylation of CYP11B2 in the adrenal glands.…”
Section: Discussionsupporting
confidence: 53%
“…We have recently shown that interleukin 6 stimulation can cause DNA demethylation of the angiotensinogen gene promoter in H295R cells. 20 In our data, switching from a low-salt diet for 4 weeks to a high-salt diet for 4 weeks decreased aldosterone synthesis and induced hypermethylation of CYP11B2 in the adrenal glands. Stimulatory signals will orchestrate local recruitment of transcription factors and global reduction in DNA methylation activity.…”
Section: Discussionsupporting
confidence: 48%
“…1). The sites were selected based on a previous study where DNA methylation of these cytosines, which are situated in a CEBP binding region, has been associated with both chromatin accessibility in human adrenocortical cells and with lower AGT expression in both humans and rats (Wang et al , 2014). Primers for PCR amplification [forward: 5′‐GGTGGTTGGTTTTAGGTTGTTATATA‐TTTA‐3′, reverse (biotinylated): 5′‐ACTATTCCCAAACTACCTATACAC‐3′] and sequencing (5′‐TGTTATATATTTA‐GGGAGATGT‐3′) were designed using the pyromark assay design 2.0 software (Qiagen).…”
Section: Methodsmentioning
confidence: 99%
“…The transcriptional activity of AGT has been found to be dependent on demethylation of the CEBP (CCAAT/enhancer‐binding protein) binding site of the AGT promoter region (Wang et al , 2014). Accordingly, the aim of this study was to investigate whether lower AGT promoter methylation in tumor tissue is predictive for glioblastoma patients not responding to bevacizumab combination therapy.…”
Section: Introductionmentioning
confidence: 99%